Understanding order flow - Evans, Martin D. D. 1960-; Lyons, Richard K. 1961- (National Bureau of Economic Research, 2005)
"This paper develops a model for understanding end-user order flow in the FX market. The model addresses several puzzling findings. First, the estimated price-impact of flow from different end-user segments is, dollar-for-dollar, quite different. Second, order flow from segments traditionally thought to be liquidity-motivated actually has power to forecast exchange rates. Third, about one third of order flow's power to forecast exchange rates one month ahead comes from flow's ability to forecast future flow, whereas the remaining two-thirds applies to price components unrelated to future flow. We show that all of these features arise naturally from end-user heterogeneity, in a setting where order flow provides timely information to market-makers about the state of the macroeconomy"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Foreign exchange rates -- Econometric models